Mediaeval commentaries on the Sentences of Peter Lombard : Volume 1, Current research. - Evans, G. R. (BRILL, 2002)
This volume deals with the development of a phenomenon of the mediaeval academic world, the adoption, after initial uncertanties, of the Sentances of 12th century Peter Lombard as the standard textbook of mediaeval theology, and the growth of literature of commentary upon it from the 13th century.